TRENDS, PATTERNS, AND GAPS IN THE IMPLEMENTATION OF MULTIPLE INTELLIGENCES IN SCHOOL LEARNING: A SYSTEMATIC REVIEW (2015–2025) - Weni Septianti; Nuni Widiarti; Arif Widiyatmoko (Universitas Islam Negeri Mataram, 2026)
This study addresses the persistent dominance of uniform instructional practices in schools that emphasize limited dimensions of intelligence and insufficiently accommodate students’ diverse cognitive characteristics. To provide a structured synthesis of existing evidence, this study aims to examine trends, patterns, and research gaps in the implementation of Multiple Intelligences (MI) in school learning from 2015 to 2025. The research employed a Systematic Literature Review (SLR) using a qualitative-descriptive approach with thematic synthesis, following the PRISMA 2020 framework. Data were retrieved from peer-reviewed journal articles indexed across multiple academic databases, including Google Scholar and ERIC, through systematic identification, screening, eligibility, and inclusion procedures, resulting in 23 empirical studies for final analysis. The findings reveal a noticeable increase in MI-related research in recent years, with strong concentration at the elementary education level and within Islamic Religious Education and Mathematics subjects. Qualitative designs remain predominant, while longitudinal and large-scale investigations are limited. Additionally, certain intelligence domains particularly musical and naturalistic intelligences remain underrepresented. These results indicate that MI implementation tends to be pedagogically adaptive yet selectively integrative rather than systemically transformative. Strengthening methodological rigor and expanding cross-level curricular integration are therefore essential for advancing more comprehensive implementation of MI in school learning.